Heterogeneous firms, R&D policies and the long shadow of business cycles - Cristiana Benedetti-Fasil; Giammario Impullitti; Omar Licandro; Petr Sedlácek (European Commission, Joint Research Centre (JRC), 2021)
Growth and business cycles have a long tradition of being studied separately. However, events such as the Great Recession raise concerns that severe downturns may have detrimental implications for growth. If so, what policies may help alleviate such long-lasting effects of large recessions? To study these questions, we develop a tractable general equilibrium model of endogenous growth featuring heterogeneous firms, financial constraints and a range of innovation policies. A preliminary analysis suggests that counter-cyclical tax credits may serve as a powerful automatic stabilizer alleviating the long-lasting negative effects of severe cyclical downturns.
Keywords: F12; F13; O31; O41; 330; Firm dynamics; innovation policy; endogenous growth; business cycles